Impact of IFRS adoption and value relevance of accounting quality on listed firms in Nigeria / Ahmad Alhaji Zubairu, Lubabatu M. Kwanbo and Abbas Usman - Zubairu, Ahmad Alhaji; M. Kwanbo, Lubabatu; Usman, Abbas (Universiti Teknologi MARA, Perlis, 2021)
This study concentrated on evaluating the value relevance of accounting quality in Nigeria both before and after the mandatory adoption of IFRS as a reporting standard for the period of two (2) years (2011-2012) using annual reports of the whole (108) companies quoted on Nigerian stock exchange with exclusion to companies that operate in the financial services sector of the market, criteria were used to arrive at the sample of 91 listed firms, Secondary data and Ordinary least Square (OLS) was engaged in analyzing the data extracted for this study, using STATA 13, Analysis was done using Pre IFRS and Post IFRS, the study discovered that value relevance of accounting quality is higher in the post-IFRS adoption period compared to that of the pre-adoption period. The study recommended that other developing nations should adopt IFRS as their financial reporting standard since it is accomplished of increasing their value relevance of accounting quality.